Facilitating Mental Health Literacy: Targeting Canadian First Nations Youth - Potvin-Boucher, Jacqueline T.; Malone, Judi L. (Canadian Counselling and Psychotherapy Association, 2014)
As reported rates of mental illness and suicide among Canadian First Nations youth continue to rise, counsellors are uniquely placed to contribute to mental health literacy. Development of contextually appropriate programs requires knowledge of the myriad of contributing factors including residual issues of colonization, discrimination, marginalization, and socioeconomic struggles that play pivotal roles in wellness and mental health risks. Given the potential contribution of such programs and the dearth of literature in this area, we reflect on what factors would contribute to facilitating or adapting existing mental health literacy programs to target Canadian First Nations youth. We explore ideas for integrating culture and context, youth engagement, and youth empowerment. Comme les taux déclarés de la maladie mentale et le suicide chez les jeunes des Premières Nations canadiennes continuent d’augmenter, les conseillers sont particulièrement bien placés pour contribuer à la littératie en santé mentale. L’élaboration de programmes adaptés au contexte nécessite la connaissance d’une multitude de facteurs en jeu, y compris les questions résiduelles de la colonisation, la discrimination, la marginalisation, et les luttes socio-économiques qui jouent un rôle essentiel dans les risques à la santé mentale et le bien-être. Compte tenu de la contribution potentielle de ces programmes et de la pauvreté de la littérature dans ce domaine, nous réfléchissons sur les facteurs qui pourraient contribuer à faciliter ou à adapter des programmes existants d’alphabétisation en santé mentale afin de cibler les jeunes Canadiens des Premières Nations. Des idées sont explorées sur l’intégration culturelle et le contexte, l’engagement des jeunes, et le renforcement de l’autonomie des jeunes.